2018
DOI: 10.1080/10408398.2018.1470491
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high-polyphenol extra virgin olive oil on cardiovascular risk factors: A systematic review and meta-analysis

Abstract: The polyphenol fraction of extra-virgin olive oil may be partly responsible for its cardioprotective effects. The aim of this systematic review and meta-analysis was to evaluate the effect of high versus low polyphenol olive oil on cardiovascular disease (CVD) risk factors in clinical trials. In accordance with PRISMA guidelines, CINAHL, PubMed, Embase and Cochrane databases were systematically searched for relevant studies. Randomized controlled trials that investigated markers of CVD risk (e.g. outcomes rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 46 publications
3
93
2
9
Order By: Relevance
“…Recently, a study carried out on 62 institutionalized elderly humans fed with EVOO showed a significant improvement of their redox status, with positive effects on lipid profiles and total antioxidant capacity, significantly increased activity of catalase in erythrocytes, and decreased activity of superoxide dismutase and glutathione peroxidase [69]. Finally, a systematic review evaluated the effect of the intake of olive oil with high or low polyphenol content on CVDs risk factors, as emerged in a number of clinical trials; the study concluded that polyphenol-rich olive oil confers some benefits resulting in reduction of CVD-risk, even though the authors claimed that more prolonged studies in non-Mediterranean populations were needed to better validate the data [70].…”
Section: The Beneficial Effects Of Plant Polyphenols Are Supported Bymentioning
confidence: 99%
“…Recently, a study carried out on 62 institutionalized elderly humans fed with EVOO showed a significant improvement of their redox status, with positive effects on lipid profiles and total antioxidant capacity, significantly increased activity of catalase in erythrocytes, and decreased activity of superoxide dismutase and glutathione peroxidase [69]. Finally, a systematic review evaluated the effect of the intake of olive oil with high or low polyphenol content on CVDs risk factors, as emerged in a number of clinical trials; the study concluded that polyphenol-rich olive oil confers some benefits resulting in reduction of CVD-risk, even though the authors claimed that more prolonged studies in non-Mediterranean populations were needed to better validate the data [70].…”
Section: The Beneficial Effects Of Plant Polyphenols Are Supported Bymentioning
confidence: 99%
“…The scanning was performed at room temperature (22 • C) and a resolution of 1 nm on the UV-Vis spectrophotometer in a quartz cuvette (1 × 1 cm). The total carotenoid content (TCC), expressed over β-carotene, was calculated according to Equation (2).…”
Section: Determination Of Total Carotenoid Contentmentioning
confidence: 99%
“…Vegetable oils are the main source of the various phenolic compounds, vitamins, tocopherols, pigments, and minerals that have a positive effect on human health [1]. The essential fatty acids (linoleic and α-linolenic acid) play an important role in brain function, proper growth, and development, reduction of inflammation and risk factors for the development of heart disease, as well as cancer and arthritis therapy [2][3][4]. The plum seeds have significant amounts of oil (about 30%) [5] that contains various bioactive compounds, including tocols, phenolic compounds [6], proteins, and lipids [7].…”
Section: Introductionmentioning
confidence: 99%
“…Olive oil and table olives are a major part of the traditional food in the Mediterranean Aliment Culture (MAC) [ 1 ]. Olives and olive oil have been found to naturally protect against stroke, degenerative and cardiovascular diseases as well as cancer and obesity [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Extra virgin olive oil is one of the essential sources of monoenoic fatty acids and biophenol (BP)-based bioactives [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Olive leaves contain a higher concentration of BPs with secos of 1450 mg/100 FW (fresh weight) compared to the olive fruit and oil, which have 110 mg/100 g and 23 mg/100 mL, respectively [ 9 ]. Oleuropein and ligstroside aglycones, oleacein, oleocanthal, hydroxytyrosil-elenolate, tyrosil-elenolate, oleoside-11-methyl ester, elenoic acid, hydroxytyrosol, and tyrosol are downstream pathway bioactives from oleuropein and ligstroside precursors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Oleuropein is the principal BPseco in green olive fruits, leaves, and table olives, whereas olive oil is rich in its downstream metabolites [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%